The Perceptions of Head's Room and Team Leader About Workload and Nurse Planning for Every Shift in Tasikmalaya City Hospital - Usman Sasyari; Miftahul Falah; Fitri Nurlina (Media Keperawatan Indonesia, 2022)
The quality of nursing care services can achieve optimal results if the workload and existing nurse resources have a balanced proportion. Currently, the quality of nursing care services is still unsatisfactory and influenced by various problems including problems of planning and scheduling nursing staff at each service shift. The purpose of this study was to identify the perception of the head’s room and team leader about the workload and planning of nursing staff at each service shift in Tasikmalaya City Hospital. The results showed that the perception of the head’s room and the team leader were mostly 20 nurses (51.3%) with good categories. The results of the survey using a questionnaire showed that the head’s room and the team leader stated that the daily workload seemed to make nurses tired and bored. Planning for nursing staff at each service shift, according to the head’s room and team leader, should be adjusted to the workload in their environment. Therefore, it is recommended to make adjustments to meet the needs of the nursing staff. Planning analysis needs to be done so that the placement of nurses in each inpatient room can be adjusted to the needs to improve health services, especially nursing services.